Genetic Research in Type 2 Diabetes: Moving Beyond GWAS - Dharambir K. Sanghera; Piers R. Blackett (Recent Updates in Disease and Health Research Vol. 4, 2024)
The present study highlights the results of recent genome-wide association studies (GWAS), which have significantly underestimated the disease heritability and present a challenge for ongoing and future investigation. Type 2 diabetes mellitus (T2D) is the fifth greatest cause of death worldwide and one of the most difficult issues of the twenty-first century. There is a lot of data to support the complex nature of T2D and its substantial hereditary component. Nearly 400 susceptibility loci linked to type 2 diabetes (T2D) and related metabolic characteristics have been effectively found and replicated by recent genome-wide association studies (GWAS), primarily in European populations but also in some African and South Asian populations. The GWAS serve as a starting point for future genetic and functional studies since the mechanisms of action by which these associated loci influence disease is still unclear, and it is difficult to predict the potential implications of these findings in clinical settings. It is imperative to develop a deeper understanding of genetic, epigenetic, environmental, cultural, and social factors that may interact to cause progression to T2D and are responsible for the declining health of the fastest developing nations of the third world. Despite extensive replication, no study has unequivocally demonstrated their clinical role in disease management beyond progression to T2D from impaired glucose tolerance. However, these studies are revealing new molecular pathways underlying diabetes etiology, gene-environment interactions, epigenetic modifications, and gene function. This review highlights evolving progress made in the rapidly moving field of T2D genetics that is starting to unravel the pathophysiology of a complex phenotype and has the potential to show clinical relevance in the near future.